2021
DOI: 10.1242/dmm.047811
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p21-activated kinase Mbt/PAK4 causes Parkinson-like phenotypes inDrosophila

Abstract: Parkinson's disease (PD) provokes bradykinesia, resting tremor, rigidity and postural instability but also non-motor symptoms such as depression, anxiety, sleep and cognitive impairments. Similar phenotypes can be induced in Drosophila melanogaster through modification of PD-relevant genes or the administration of PD-inducing toxins. Recent studies correlated deregulation of human p21-activated kinase PAK4 with PD, leaving open the question of a causative relationship of mutations in this gene for manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 124 publications
(284 reference statements)
1
14
0
Order By: Relevance
“…The fact that rescue was not complete could be due to a dominant negative effect of the mutation, as suggested by enzymatic assays on extracts of heterozygous Aprt 5 mutants (Figure S4). Previous work from our and other laboratories showed that DA neurons control the SING behavior in Drosophila (Feany and Bender 2000; Friggi-Grelin et al 2003; Riemensperger et al 2011; Vaccaro et al 2017; Sun et al 2018) and that PAM DA neuron degeneration induce SING defects in various Parkinson’s disease models (Riemensperger et al 2013; Bou Dib et al 2014; Tas et al 2018; Pütz et al 2021). Here, we found that knocking down Aprt either in all DA neurons or only in the PAM DA neurons was sufficient to induce early SING defects.…”
Section: Discussionmentioning
confidence: 85%
“…The fact that rescue was not complete could be due to a dominant negative effect of the mutation, as suggested by enzymatic assays on extracts of heterozygous Aprt 5 mutants (Figure S4). Previous work from our and other laboratories showed that DA neurons control the SING behavior in Drosophila (Feany and Bender 2000; Friggi-Grelin et al 2003; Riemensperger et al 2011; Vaccaro et al 2017; Sun et al 2018) and that PAM DA neuron degeneration induce SING defects in various Parkinson’s disease models (Riemensperger et al 2013; Bou Dib et al 2014; Tas et al 2018; Pütz et al 2021). Here, we found that knocking down Aprt either in all DA neurons or only in the PAM DA neurons was sufficient to induce early SING defects.…”
Section: Discussionmentioning
confidence: 85%
“…We and others have previously shown the loss of dopaminergic neurons (DA) within the protocerebral anterior medial (PAM) cluster by genetic or pharmacological insults in adult Drosophila brains [11,1719]. Although the number of PAM neuron loss observed so far varies between 15% and 80%, other DA clusters remain unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila brains [11,[17][18][19]. Although the number of PAM neuron loss observed so far varies between 15% and 80%, other DA clusters remain unaffected.…”
Section: We and Others Have Previously Shown The Loss Of Dopaminergic...mentioning
confidence: 98%
“…The p21 activated kinase Pak4 plays a pivotal role in neuronal pathophysiology, promoting the activity of transcription factors involved in cell survival, such as Akt and Cepbp and, thus, contributing to a wide range of intracellular processes including cytoskeletal dynamics, neuronal development, axonal outgrowth and neuronal survival [ 49 , 50 , 51 ]. Down-regulated expression of Pak4 has been associated with neurodegenerative disorders, including Amyotrophic Lateral Sclerosis and Parkinson’s disease, and it has been proposed as a therapeutic target against cancer and neurodegeneration [ 52 , 53 , 54 , 55 ]. Nerve growth factor receptor Ntrk1 promotes neuronal survival, proliferation and differentiation in neuronal populations, representing a clinically relevant target in neurology [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Systems Biology Approaches To Explore the Transcriptional Pr...mentioning
confidence: 99%